Like Devils out of Hell': Reassessing the African Presence in Early Modern England - Lewis, Tamara E. (Black theology, 2016)
Early modernists have traditionally argued that Black representations in English Renaissance art and literature did not reflect the historical presence of persons of color. In contrast, documentary research has uncovered Africans in England as early as 1500. From that time, the existence of a substantial African population was erased from contemporary histories in order to suppress knowledge of England's participation in the transatlantic slave trade. Separation of the Church of England from Rome had exacerbated political and economic conflict with Catholic nations, particularly Spain. Protecting the Protestant English state image became a primary concern. Despite national and theological differences, English monarchs and law courts appropriated Roman Catholic pronouncements on the relationship between Blackness and religion. This paper demonstrates the intersection of political and economic factors with theological discourse and emergent conceptions of race at a defining moment in English history.